Analisis Potensi Wilayah Pengembangan Peternakan Sapi Perah di Kabupaten Enrekang - St. Aisyah R; Asriyanti Syarif; Sitti Khadijah Yahya Hiola (JURNAL GALUNG TROPIKA, 2021)
This study is to analyze the potential of the area for developing dairy cattle in Enrekang Regency using a descriptive method. Primary data was obtained from direct interviews with dairy farmers and secondary data collected was periodic data over five years, from 2017 to 2021, sourced from the Central Bureau of Statistics of Enrekang Regency. The data analysis used is qualitative analysis and location quotient (LQ). The results show that the areas that become the economic base in the development of the dairy cattle business are Cendana District and Anggeraja District. The obstacles experienced by dairy farmers so far are the availability of cattle breeds, the availability of feed, health services, marketing, and human resources. The dairy farming business in Enrekang Regency can be maximized to be able to be competitive.